A comprehensive assessment of phenotypic diversity, multivariate relationships, and trait associations in wild oil palm (Elaeis guineensis) collections in Ghana - DICKSON OSEI DARKWAH; DANIEL AGYEI-DWARKO; SAMUEL ADU OSEI; BRIGHT FIAWONA; SAMUEL BANAFO; JOHNNY OSSOM SACKITEY; ENOCH SAPEY (Smujo International, 2026)
Abstract. Darkwah DO, Agyei-Dwarko D, Osei SA, Fiawona B, Banafo S, Sackitey JO, Sapey E. 2026. A comprehensive assessment of phenotypic diversity, multivariate relationships, and trait associations in wild oil palm (Elaeis guineensis) collections in Ghana. Asian J Agric 10 (1): g100173. https://doi.org/10.13057/asianjagric/g100173. The CSIR-Oil Palm Research Institute in Ghana conserves 135 wild oil palm (Elaeis guineensis) accessions in its ex-situ gene bank. Due to the narrow genetic base of current Deli dura breeding populations, this study aimed to evaluate the phenotypic diversity and breeding potential of these accessions using multivariate analysis. An augmented experimental design with two replicated Deli dura checks was used to assess 25 agro-morphological traits. Data were analyzed using analysis of variance, cluster analysis, principal component analysis, and Pearson’s correlation in R software. Significant variation was observed among accessions for 20 traits. High genotypic coefficient of variation, heritability, and genetic advance as percentage of mean were recorded for fresh fruit bunch yield (25.42%, 90.76%, 49.96%), bunch number (24.32%, 80.18%, 44.92%), and average bunch weight (20.01%, 83.44%, 37.70%). Cluster analysis grouped the accessions into four major clusters independent of geographic origin. Seven principal components with eigenvalues greater than one explained 82.66% of the total phenotypic variation, while both positive and negative trait associations were observed. The findings reveal substantial phenotypic diversity among Ghanaian wild oil palm collections, highlighting their potential for breeding, genetic base broadening, germplasm conservation, and future core collection development, pending validation with molecular markers.